Contemplations on the implementation of the African charter on democracy, elections and governance: fostering elections and democratic institutions in Ethopia and Lesotho - Jena, Gillian Runyararo (My University, 2017)
This study examines the effectiveness of the African Charter on Democracy, Elections and Governance in promoting free and fair elections, focusing on Electoral Management Bodies established and operational in Ethiopia and Lesotho. It assesses practical missions conducted by the EMBs within the three levels of electoral governance theoretical framework; that is rule making, rule application and rule adjudication. This study has significant effects for consolidation of democracy and governance because the democracy discourse recognizes important correlations between quality of elections administered by democratic institutions and governance. The study established that both Ethiopia and Lesotho partially implemented the ACDEG electoral rules due to varying political wills, and that the nations’ EMBs were incompetent and faced logistical challenges. However, Ethiopia’s reluctance to genuinely incorporate and enforce the ACDEG principles within its Electoral Law limited the capacity of the NEBE to manage the 2010 and 2015 elections. Whilst Lesotho’s IEC functioned in an inadequate manner due to recurring political unstable contexts it operated within. Both Ethiopia and Lesotho encountered various electoral challenges notably, evident vote inflation, intimidation, violent incidences, unfair media coverage for opposition parties, unreliable voter registers and unsecured ballot boxes which continue to discredit elections. This study posits that the ACDEG effective implementation in promoting free and fair elections can be fruitful with constant dedication by signatory state parties’ to entirely domesticate ACDEG electoral rules in national laws; maintain impartial EMBs and cooperate with election monitors under a regulated compliance mechanism by the African Union. This would address common electoral challenges tormenting African nations; and aid to prevent non-adherence by state parties who devalue the African Union’s election regulations they willingly acceded to.
A Theses submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the Master of Arts Degree in International Relations, October 2017
Keywords: Elections--Africa; Political participation--Africa; Democracy--Africa; Africa--Politics and government; Africa--Politics and government